Response of a marine benthic invertebrate community and biotic indices to organic enrichment from sewage disposal. (28th October 2019) - Culhane, Fiona E.; Briers, Robert A.; Tett, Paul; Fernandes, Teresa F.
Abstract: Nutrient enrichment is a significant cause of ecosystem change in coastal habitats worldwide. This study focuses on the change in a benthic macroinvertebrate community and environmental quality as assessed through different biotic indices following the construction of a sewage outfall pipe in the west of Scotland, from first implementation to seven years after operation of the pipe. Benthic macroinvertebrates are an important part of marine ecosystems because they mediate ecosystem processes and functions, are a key part of food webs and they provide many ecosystem services. Results indicated a clear change in benthic communities over time with an increase in species richness and changes to benthic community composition (specifically feeding type, bioturbation mode and ecological group) towards those indicative of organic enrichment. No clear spatial zonation was observed because organic carbon content increased over the entire area. According to a suite of benthic indices calculated, some negative changes were detectable following the start of sewage disposal, but largely negative community changes, and a change from 'good' to 'moderate' quality, only occurred seven years after implementation. The increase in species richness in response to increasing disturbance reduced the utility of a multi-metric index, the Infaunal Quality Index, which, instead of amplifying the signal of negative impact, dampened it. We suggest that any change in communities, regardless of direction, should be heeded, and species richness is a particularly sensitive and early warning indicator for this, but a suite of approaches is required to understand benthic community changes.